Crossmodal integration in the primate superior colliculus underlying the preparation and initiation of saccadic eye movements. - Bell, A; Meredith, M; Van Opstal, A; Munoz, D (2005)
Saccades to combined audiovisual stimuli often have reduced saccadic reaction times (SRTs) compared with those to unimodal stimuli. Neurons in the intermediate/deep layers of the superior colliculus (dSC) are capable of integrating converging sensory inputs to influence the time to saccade initiation. To identify how neural processing in the dSC contributes to reducing SRTs to audiovisual stimuli, we recorded activity from dSC neurons while monkeys generated saccades to visual or audiovisual stimuli. To evoke crossmodal interactions of varying strength, we used auditory and visual stimuli of different intensities, presented either in spatial alignment or to opposite hemifields. Spatially aligned audiovisual stimuli evoked the shortest SRTs. In the case of low-intensity stimuli, the response to the auditory component of the aligned audiovisual target increased the activity preceding the response to the visual component, accelerating the onset of the visual response and facilitating the generation of shorter-latency saccades. In the case of high-intensity stimuli, the auditory and visual responses occurred much closer together in time and so there was little opportunity for the auditory stimulus to influence previsual activity. Instead, the reduction in SRT for high-intensity, aligned audiovisual stimuli was correlated with increased premotor activity (activity after visual burst but preceding saccade-aligned burst). These data provide a link between changes in neural activity related to stimulus modality with changes in behavior. They further demonstrate how crossmodal interactions are not limited to the initial sensory activity but can also influence premotor activity in the SC.